A crítica musical dos anos 1960 e o processo de construção da MPB: uma análise da coluna Música Popular , de Torquato Neto - Ribeiro, Janaina Faustino (2010)
Owing to the relevance of the critical nature of institutions for the construction of legitimate Western cultural history, this dissertation aims at developing an investigation on strategies and mechanisms utilized by the Brazilian music critics of the 60 s within the MPB (Brazilian popular Music) category. The privileged object for such analysis will be the editorial column called Popular Music published in Jornal dos Sports between March and October of 1967 by Torquato Neto. The starting point of this work is the critique itself, at a certain extent since it constitutes a part of the broad intellectual project, which attempted to insert the country into the modernity as well as define its national basis since the 19th century. Thus, a second hypothesis is found, which is that critics assumed a role of legitimate representation channel of the produced Brazilian music at that time. It must be considered, though, that there were some debatable issues regarding the establishment of the Brazilian Popular Music. Some of these issues are the elaboration of distinct projects of Brazilianness and the attempt to connect the whole country through culture and eventually through music. In this very process, valuation criteria are carefully taken into consideration because they were the parameters for Torquato s judgement. Among the important references which deserve to be seriously explored for the problem investigation of values are Pierre Bourdieu and Steven Connor. By so doing it, it will be possible to understand some processes such as: how some artists eventually stood out from the others, how prestige arose from the Brazilian socio-cultural hierarchy and how distinctive criteria were established in the 60 s in order to classify the Brazilian popular Music (MPB) a musical style of good taste . An analysis of how this generic category was based on names and how the Bossa Nova artists contributed to the consolidation of the memory inherited from the identity of the popular music in the country will be conducted.